People and great deeds - Beckwith, Yvonne (Chicago, Ill. : Child's World, 1971)
Brief biographies of twenty-three famous people in history include Galileo, Mozart, Helen Keller, Marie Curie, and Thomas Jefferson.
Keywords: Biography -- Juvenile literature; Biography